Bargaining with the State. - Epstein, Richard Allen, 1943- (Princeton University Press, 2001)
Bargaining with the State examines the threats to liberty that arise through the power of government selectively to distribute benefits and favors to its citizens. For Richard Epstein, the preservation of individual liberty against government contractual power advances not only the short-term interest of the individual citizen but also the long-term overall social welfare.